(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to investigation of formation of pedagogical culture of a foreign language teacher in the system of higher education. The author proves that pedagogical competence is formed through the implementation of the components of the teacher’s personal qualities and professional content, which interact with each other in the educational process.